STUDI DESKRIPTIF RISIKO KANKER PAYUDARA PADA KELOMPOK BERISIKO DAN TIDAK BERISIKO DI RUMAH SAKIT UMUM PUSAT SANGLAH 21 – 26 NOVEMBER 2013 - Bosman Ariesta, I Gusti Putu Benediktus; Wibawa Manuaba, Ida Bagus Tjakra (E-Jurnal Medika Udayana; vol 4 no 12(2015):e-jurnal medika udayana, 2015)
DESCRPTIVE STUDY: BREAST CANCER RISK AMONG RISK GROUP AND NON RISK GROUP IN SANGLAH HOSPITAL  NOVEMBER 21 st – 26 th 2013 This study evaluates the lifetime risk and BRCA1 and BRCA2 genes mutation risk between risk group and non-risk group. This is a descriptive study. Total 100 respondents according to inclusion criteria are included in this study. The data is obtained from the interview about personal identity and research variable. The calculation of the risk is based on each validated model and analyzed by SPSS 16 for Windows. Average of lifetime risk for risk woman, based on Gail, Claus, Claus Extended, and Cuzick-Tyrer model are 7,85%, 12,82%, 13,13%, dan 14,76% respectively. Average of lifetime risk for non-risk woman based on Gail and Cuzick-Tyrer model are 4,15% and 7,92% respectively. Average mutation risk of BRCA1 and BRCA2 in risk woman are 0,43% dan 0,61% respectively, meanwhile in non-risk woman are 0,07% dan 0,13% respectively. Mutation risk of population are 0,12% and 0,2% respectively. This study suggest higher average of lifetime risk between risk woman and non-risk woman. The risk group have higher mutation risk than population risk, and the non-risk group have lower mutation risk than population risk both BRCA1 and BRCA2.
Keywords: breast cancer; lifetime risk; mutation risk